Negotiating Islam with cinema; A theoretical discussion on Indonesian Islamic films - Huda, Ahmad Nuril (UI Scholars Hub, 2012)
This paper aims at exploring certain negotiations that justify Muslim's cinematic texts and practices. It focuses on the questions about what is Islamic and un-Islamic about film, who and what decides certain films as Islamic, and what are the meanings of cinematic practices of Islam for Muslim society. Furthermore, this paper tries to investigate these questions from a theoretical basis using concepts of Islamic modernity, Islamic Ummah and Public, in order to shed some light on the idea of how a production of an Islamic film may trigger the creation of a political and religious identity.